The art of racing in the rain : [compact disc, unabridged] a novel - Stein, Garth (Harper Audio, 2008)
Evaluating his life on the eve of his death, atypical canine Enzo considers the sacrifices his master, Denny Swift, has made in his pursuit of becoming a professional race car driver, and the dog's own efforts to preserve the Swift family.